Uncertainty, Likelihoods and Investment Decisions - Angell, James W. (Quarterly Journal of Economics, 1960)
Introduction, 1. — I. The problem of “explanation,” 3. — II. Shackle's hypothesis, 4. — III. An alternative hypothesis. The “most likely” gain outcome, 7. — IV. The “most likely” loss outcome, 15. — V. Evaluating net prospective satisfactions; “gambler preference maps,” 16. — VI. Holding money; alternative investments; marginal equalities, 19. — VII. Limitations, 24. — VIII. Business decisions, 25. — IX. Waves of optimism and pessimism, 27.